Is There a New Paradigm of Dryland Development? - Mortimore, Michael (Annals of Arid Zone, 2016)
This paper takes a developmental approach to land degradation in dry lands. There is a large knowledge bank on the science and technology of 'desertification', which has tended until recently to overly influence dryland development policy. This resource does not translate automatically into appropriate policies or development interventions, as shown by the poor record of 'desertification control' over the past half-century. There have been failures to impact on the scale expected either on poverty or on natural resource management. While there is still scope for further advancing the scientific understanding of land degradation, a review of the West African experience has highlighted the priorities of (i) understanding 'success stories' of dryland development, (ii) overcoming the constraints which block new or improved technologies through strengthening incentives for investment, and (iii) aligning development policy with dryland peoples' strategies to diversify their incomes and develop inter-regional linkages. It is therefore argued that a developmental approach is needed, in order to integrate science with policy making, as well as to identify priorities for research in future.